Palpitations in Women With Breast Cancer Are Associated With Polymorphisms for Neurotransmitter Genes. - Ying Sheng; Conley, Yvette P.; Paul, Steven M.; Cooper, Bruce A.; Carpenter, Janet S.; Hammer, Marilyn J.; Levine, Jon D.; Miaskowski, Christine (Oncology Nursing Forum, 2024)
OBJECTIVES: To evaluate for associations between the occurrence of palpitations reported by women prior to breast cancer surgery and single nucleotide polymorphisms (SNPs) for neurotransmitter genes. SAMPLE & SETTING: A total of 398 women, who were scheduled for unilateral breast cancer surgery, provided detailed information on demographic and clinical characteristics and the occurrence of palpitations prior to breast cancer surgery. METHODS & VARIABLES: The occurrence of palpitations was assessed using a single item (i.e., "heart races/pounds" in the past week ["yes"/"no"]). Blood samples were collected for genomic analyses. Multiple logistic regression analyses were used to identify associations between the occurrence of palpitations and variations in neurotransmitter genes. RESULTS: Nine SNPs and two haplotypes among 11 candidate genes were associated with the occurrence of palpitations. These genes encode for a number of neurotransmitters and/or their receptors, including serotonin, norepinephrine, dopamine, gammaamino butyric acid, Substance P, and neurokinin. IMPLICATIONS FOR NURSING: These findings suggest that alterations in a variety of neurotransmitters contribute to the development of this symptom.